Pembelajaran Berbasis Pendidikan Multikultural pada Sekolah Indonesia Luar Negeri di Malaysia dan Singapura - Nurmanita, Tiara Sevi; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Anam, Khaerul; Suparti, Suparti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to analyze the teaching and learning process at Indonesian Schools (SILN), focusing on the challenges faced in preserving Indonesian cultural heritage amidst the social, cultural, and linguistic diversity of students from diverse backgrounds. The research method used here is qualitative, based on a case study approach, and employs thematic analysis to analyze the collected data. The research team conducted in-depth interviews with school administrators, faculty, and students from Indonesian Schools in Kota Kinabalu (SIKK), Kuala Lumpur (SIKL), and Singapore (SIS) to gather information about the curriculum and pedagogy at SILN. Education at Indonesian schools abroad must be integrated with the teaching of Indonesian culture and the learning of the Indonesian language, which directly contributes to the formation of national character. The study findings are anticipated to provide theoretical contributions to the development of multicultural education and Indonesian language teaching abroad, as well as practical benefits for SILN administrators and teachers in developing more effective and inclusive teaching methods, thereby enabling education at SILN to optimally maintain and introduce Indonesian culture to students living abroad. Keywords: Global Diversity, Multicultural Education, Teaching and Learning Process, Indonesian Schools Abroad